APPLICATION OF DIDACTIC BUSINESS GAMES IN CHEMISTRY LESSONS THEIR (ResearchJet Journal of Analysis and Inventions, 2023)
The article deals with the didactic conditions for the use of business games in chemistry lessons, i.e. gradual development of activities in a business game, the need for conflict situations for the game, taking into account the interaction of students during the game.about the need to control the time of the game, the presence of competitive elements in the game, the need to evaluate the results of the game.